New insights into the activation mechanism of calcium species to quartz: ToF-SIMS and AFM investigation. (1st July 2020) - Luo, Ximei; Lin, Qiqiang; Wang, Yunfan; Tian, Mengjie; Lai, Hao; Bai, Shaojun; Zhou, Yongfeng
Highlights: Surface coverage thickness of Ca 2+ on quartz increased as pH increased. The coverage density of sodium oleate on quartz at different pH levels varied. ToF-SIMS and AFM studies supported the importance of the thickness and density of Ca 2+ coverage. Quartz was activated by Ca 2+, forming C18 H33 O2 Ca on the surface. Preparation methods of AFM samples without a complete cleavage plane were introduced. Abstract: In this work, the activation mechanism of calcium species on the α-quartz surface was investigated. Microflotation, zeta potential measurements, first-principle calculation based on density functional theory (DFT), time-of-flight secondary ion mass spectrometry (ToF-SIMS) measurements and atomic force microscope (AFM) were conducted in this investigation. Sample preparation methods for minerals without a complete cleavage plane and reagent adsorption determination were introduced. Results revealed that quartz could be activated by calcium ions at the pH above 10, and calcium ion concentrations at pH below 10 slightly affected quartz recovery. Ca 2+ could repel the hydration shell and hydroxylation on the quartz and be preferentially adsorbed onto the quartz surface at an alkaline pH. However, the coverage thickness and density of Ca 2+ and the relevant coverage density of sodium oleate increased as the pH increased. The adsorbed amounts in the horizontal and vertical directions were also not uniform. The surface coverage thickness and density of Ca 2+ and the corresponding amount of adsorbed sodium oleate played an important role in the activation of quartz. When the pH was above 10, the thickness and density of Ca 2+ coverage on the quartz surface was sufficient, and Ca 2+ could subsequently react with sodium oleate forming C18 H33 O2 Ca. Thus, the quartz hydrophobicity was improved.